CADETS AND JUNIORS SUCCESS: HOW IMPORTANT IS IT FOR SPORTS CAREERS IN FREE-STYLE WRESTLING? - Latyshev, Mykola; Latyshev, Sergii; Kaupuzs, Aivars; Kvasnytsya, Oleh; Tropin, Yura; Kvasnytsya, Irina; Prystynskyi, Volodimir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The successful and effective management of sports training is impossible without the justified forecasting, which is adequate to the modern scientific knowledge. The forecasting creates the necessary preconditions for correct management decisions by athlete, coaches and administration. Nowadays, the discovery of talented athlete and the ways of their improvement are among the most discussed and popular directions in the athletes’ training. The aim of the research –to analyze the significance of the success of wrestlers at the cadet and junior levels on the performance results during the senior career in relation to the weight classes. The sports careers of the medalists in freestyle wrestling of the Cadets and Junior European Championships have been studied. The analysis of the cadets’ results demonstrates that more than 30% of the athletes have taken part in seniors competitions, but unfortunately only under 15% of the athletes have achieved success. At the same time, the juniors’ results are better: about 60% of the athletes continued their sports careers at the senior level, but only approximately 25% have achieved significant results. It is demonstrated that the athletes of the lightweight classes adapt faster to the senior wrestling and achieve success at the senior level.